Evaluasi terhadap Alat Bird Deterrent dalam Menangani Hewan Burung di Sisi Udara pada Bandar Udara Internasional Sultan Hasanuddin Makassar - Teguh Ari Rahman; A. Ahmad Baso Farhan Arifuddin; Rifqi Raza Bunahri; Pahotan Ferry Roy Nainggolan; Tiara Nugrahayani (SKY EAST: Education of Aviation Science and Technology, 2024)
This research evaluates the effectiveness of bird deterrent devices in dealing with the problem of birds on the airside at Sultan Hasanuddin International Airport, Makassar. The background of this research was driven by the need to ensure flight safety by controlling birds that often disturb the area. One of the solutions used is the bird deterrent device, but its effectiveness in repelling birds was not optimal. This research uses a qualitative descriptive method with a direct observation approach, structured interviews with related parties, and documentation in the field. The results of the research indicated that the bird deterrent device used is not fully effective in repelling birds. One of the main reasons is the less-than-optimal sound frequency setting, that makes it unable to repel birds effectively in several red zone areas. Based on these findings, the research recommends increasing the frequency and sound settings of the bird deterrent device, as well as allocating the bird deterrent device to strategic locations so that the device functions effectively. With these steps, it is hoped that flight safety can further reduce incidents that threaten flight safety and bird disturbances can be minimized significantly at Sultan Hasanuddin International Airport, Makassar.